The Impact of a Broken Home Family on Children's Social Deviant Behavior - Lesmana, Gusman; Nurjamilah, Kharisma; Amalia, Dini (Berpusi Publishing, 2023)
This research aims to examine the effects of broken families on children's social behavior. The methodology used for this research is based on literature review. Research results show, among other things, that the family plays an important role in the education and development of children's rights. However, when families are not functioning well, especially in broken families, it will have an impact on children. Children experience many emotions when they experience family breakdown, including: (1) being vulnerable and psychologically disturbed; (2) hate their parents; (3) is exposed too quickly to adverse environmental effects; (4) regard life as meaningless. ; (5) it is not easy to live with; and (6) having behavioral problems (7) Lack of self-esteem (8) The emergence of feelings of not paying attention to mental health (9) Showing hatred by destroying youth (10) Don't worry about yourself.